Mechanical properties and microstructural analysis of an AgPd alloy cast under different temperatures - Olivieri, Karina Andrea Novaes; Neisser, Maximiliano Piero; Bottino, Marco Antônio; Miranda, Milton Edson; Wernek, Rafael Dario (Brazilian Dental Science, 2010)
The metal restorations are used in Dentistry a long time ago. Nowadays we have resources that can get casting more accurate, with new material and equipments and techniques more precise. The purpose of this study was to evaluate the metallurgical and mechanical aspects of the AgPd dental alloy when it was submitted to different casting temperatures. It was used 30 specimens, divided in three groups (n=10): a) control group (no cast); b) casting temperature in accordance with the manufactures’ instructions (T1); b) casting temperature above manufactures´ instructions (like a torch) (T2). It was evaluated chemical and metallographic aspects, mechanical properties and Vickers hardness. The results showed a microstructure similar to T1 and T2 conditions, but with greater amount of light phase and particles in this last one. It was observed that the rupture tensile strength for the T1 condition was greater than the T2. The alloy in the no cast condition presented greater hardness but there was no statistically significant difference between T1 and T2. Supporting by the metallographic and mechanical results, it may predict that when elevated temperatures was used, above manufacture´s recommendations, it can occur failures in the prosthesis, like porosities, fissures or cracks.